Analisis Performa Auxiliary Plate-Fin Cooler (Hayden 679) dalam Menjaga Stabilitas Termal Automatic Transmission Fluid pada Mesin Diesel - Zulfikar Nadirsyah; Muhamad Safi'i; Althesa Androva (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Automatic Transmission Fluid (ATF) degradation due to high thermal loads is the main cause of automatic transmission failure in high-torque diesel vehicles. This study aims to analyze the effectiveness of installing an external plate-fin oil cooler (Hayden 679) in maintaining ATF thermal stability. The test object used was a Chevrolet Captiva Diesel 2.0L VCDi with a 6-speed automatic transmission. ATF temperature data was acquired in real-time via the OBD-II protocol under heavy load conditions (road gradient > 15° and a constant speed of 110 km/h). The results showed that the auxiliary cooler was able to limit the maximum ATF temperature to 79°C, which is within the ideal range of 70–90°C. When compared to the standard system that reaches > 90°C, a peak temperature reduction of 14°C was obtained, which represents a thermal reduction efficiency of 15.05% and a heat dissipation of 1.4 kW. It was concluded that the use of Hayden 679 was effective in improving the thermal stability and durability of diesel transmission components.